Hypoxia And Acidosis Induce The Release Of Plasminogen Activator From Vessel Walls - Tappy, L; Bachmann, F (Thrombosis and Haemostasis, 1981)
The mechanisms, which induce the release of vascular plasminogen activator (VA), are not fully understood. To test the effects of hypoxia and of acidosis on the liberation of VA fran the vessel wall, we have used the isolated pig ear perfusion system described by Markwardt and Klöcking. Pig ears, collected at the slaughterhouse, were kept on ice for a maximum of 4 hours. A catheter was placed into the main artery and the ear flushed with oxygenated HEPES-Tyrode’s solution pH 7,4 for 30 min at 37 °C. Baseline activities in effluent fractions from time 30-42 min, averaged 0,95 U UK/ml. Assays were performed on plasminogen rich fibrin plates. Frcm 43 to 65 min, pig ears were perfused with oxygenated HEPES-Tyrode's solution pH 7,4 (controls) or pH 6,7 (acidosis), or within the same buffer (pH 7,4) pretreated by extensive nitrogen bubbling (hypoxia).VA concentrations in controls remained fairly constant until 65 min. The hypoxia stimulus resulted in an increase of PA activity of 180% over basal activity (p < 0,001). Acidosis led to a mean increase of PA activity of 240% (p < 0,001)These experiments suggest that acidosis and hypoxia, if present distally to venous segments occluded by a thrombus, may represent powerful stimuli for the secretion of plasminogen activator frcm vessel walls.